Study on fused/cast AZS refractories for deployment in vitrification of radioactive waste effluents - Sengupta, Pranesh; Mishra, Raman K.; Soudamini, N.; Sen, D.; Mazumder, S.; Kaushik, Chetan P.; Ajithkumar, Thalasseril G.; Banerjee, K. (Journal of Nuclear Materials, 2015)
Fused/cast Al2O3-ZrO2-SiO2 (FC-AZS)' is being considered as `glass contact refractory' within ceramic melters, to be used for nuclear waste immobilization. Microstructural analyses reveal random distributions of baddeleyite (ZrO2) within aluminosilicate (Al2SiO5) matrix. Al-27 and Si-29 NMR data suggest that within aluminosilicate matrix Al occurs in both 4- and 6-fold co-ordinations whereas Si prefers a 4-fold environment. Polydispersity of pores has been studied with small-angle neutron scattering (SANS) technique. Corrosion rates of FC-AZS within 6 M HNO3, simulated wastes (500 h exposure), and borosilicate melt (975 degrees C, 800 h exposure) are found to be 0.38 x 10(3) mu my(-1), 0.13 x 10(3) mu my(-1) and 4.75 x 10(3) mu my(-1) respectively. A comparison of chemical interaction data clearly suggests that FC-AZS exhibits better chemical durability than AZC refractory (Al2O3-ZrO2-Cr2O3, also used for similar purpose). Thermal cycling studies indicate that FC-AZS retains structural integrity (including compressive strength and density) even up to 20 cycles. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Interaction between refractory material and hazardous liquid; Nuclear waste immobilization; Vitrification melter

Structure and short time degradation studies of sodium zirconium phosphate ceramics loaded with simulated fast breeder (FBR) waste - Ananthanarayanan, A.; Ambashta, R. D.; Sudarsan, V.; Ajithkumar, T.; Sen, D.; Mazumder, S.; Wattal, P. K. (Journal of Nuclear Materials, 2017)
Sodium zirconium phosphate (NZP) ceramics have been prepared using conventional sintering and hot isostatic pressing (HIP) routes. The structure of NZP ceramics, prepared using the HIP route, has been compared with conventionally sintered NZP using a combination of X-ray diffraction (XRD) and (P-31 and Na-23) nuclear magnetic resonance (NMR) spectroscopy techniques. It is observed that NZP with no waste loading is aggressive toward the steel HIP -can during hot isostatic compaction and significant fraction of cations from the steel enter the ceramic material. Waste loaded NZP samples (10 wt% simulated FBR waste) show significantly low can -interaction and primary NZP phase is evident in this material. Upon exposure of can -interacted and waste loaded NZP to boiling water and steam, P-31 NMR does not detect any major modifications in the network structure. However, the Na-23 NMR spectra indicate migration of Na+ ions from the surface and possible re -crystallization. This is corroborated by Small -Angle Neutron Scattering (SANS) data and Scanning Electron Microscopy (SEM) measurements carried out on these samples.